Repertórios discursivos sobre cotas raciais e suas implicações no tratamento de alunos cotistas - Tavares, Talita Leite (2012)
This study is inserted into the context of Affirmative Action (AA) from racial quotas type in public higher education institutions. Thus, towards the profound discrimination against blacks in Brazil, the objective of this dissertation was to investigate the possible relationship between the discursive repertories about racial quotas and the perception of discrimination against black quota holders. For this purpose, it was developed two studies supported by theoretical constructs about the new forms of prejudice and racism. In Study 1, it was investigated the discursive repertories of university students about quotas for blacks in public higher education institutions. University students (n = 105), most female (55%) aged between 18 and 58 years (m = 23.6, sd = 6.79) answered a questionnaire consisting of socio-demographic questions, and an open question, considering the students opinion facing racial quotas. The Alceste software analysis revealed three major discursive classes showing opposition to racial quotas. The more representative speech (Class 3 63.20%) explained the opposition to quotas based on the idea that blacks and whites are equal. Study 2, with an almost experimental profile, aimed to analyze how discursive contexts about the implementation of racial quotas in public higher education institutions could relate to the high school students opinion (n = 581) - from public and private schools in João Pessoa / PB - facing the possibility of discrimination of quota students. Most were students from private schools (52%) and women (57%), age variation from 15 to 35 years old (m = 17; sd = 1.16), having responded to an instrument composed of socio-demographic questions and three questions about how the quota holder could be treated, respectively, by teachers, colleagues and employers. From the content analysis of the participants answers, six categories were given: holders are less capable, we are all equal, quotas are unfair, there will be prejudice, depends on the holders ability, depends on the other (employer/colleague/teacher). However, no significant effect on the types of discursive contexts in the categories that emerged about the treatment of colleagues was found [χ ² (12) = 13.614; p = 0.326] and teachers [χ ² (15) = 9.988; p = 0.820]. There was a significant effect only in the types of discursive contexts of treatment on the categories of employers [χ ² (12) = 34.909; p < 0,001]. It was found a significant effect of school type in the categories about the treatment of colleagues [χ ² (4) = 116,839; p < 0.001], teachers [χ ² (5) = 102.775; p < 0.001] and future employers [χ ² (4) = 41,632, p < 0.001]. Thereby, social belonging, being from public or private school, was more important to explain the treatment to the quota holder than the types of speeches about quotas. Overall, the results of this research reported, on the one hand, that resistance to the implementation of affirmative policies for blacks has speeches that justify its use based on equality to legitimize inequality between blacks and whites. On the other hand, the evidence that there will be prejudice against the quota holder suggests the social relevance of this study to develop strategies to combat prejudice and discrimination against black quota holders.